The effects of saline irrigation water and cobalt on growth and chemical composition in Nigella sativa - KHALID A. KHALID; MAHMOUD R. SHEDEED (Nusantara Bioscience, 2014)
Abstract. Khalid KA, Shedeed MR. 2014. The effects of saline irrigation water and cobalt on growth and chemical composition in Nigella sativa.Nusantara Bioscience 6: 146-151. Increasing plant salinity tolerance is a focus of research and industry since salinity and yield are of major concern to maximize medicinal and aromatic plant production in arid and semi-arid areas. Therefore, the present study aimed to decrease the harmful effect of salinity on Nigella sativa L plants by adapting them to saline soil stress through the use of Cobalt. The effects of saline irrigation water and cobalt on the vegetative growth characters [plant height (cm), leaf number (plant-1), branch number (plant-1), capsule number (plant1), herb dry weight (plant-1) and seed yield (plant-1)] and content of fixed oil, soluble sugars, proline, N,P,K and protein of black seed (Nigella sativa L.) plants were investigated. In these experiments, two factors were considered: saline irrigation water and Cobalt. The experimental design followed a complete random block design. The averages of data were statistically analyzed using 2-way analysis of variance (ANOVA-2) and the values of least significant difference (LSD) at 5%. Saline irrigation water decreased certain growth characters, fixed oil, protein and mineral content (N, P, and K) as saline irrigation water level increased. Saline irrigation water promoted the accumulation of soluble sugars and proline contents. The plants treated with saline irrigation water containing cobalt resulted in higher plant growth characters and chemical constituent’s values than those treated with saline irrigation water alone.